Krytyczne myślenie i logika formalna w badaniach literaturoznawczych na przykładzie wybranych utworów Ignacego Krasickiego - Magryś, Roman (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Formal logic and critical thinking are complementary tools in research of literary texts. Critical thinking is especially useful in the case of works which are antinomic in character as they are based on disputable ironic meeting points. Ignacy Krasicki’s satires are such type of text. A special difficulty is posed by the interpretation of Journey of a Warmian bishop, as the work read separately and with the use of particular contexts assumes ambiguous meanings. The application of the methodology of critical thinking, which is based on multisided approach to text, leads to the conclusion that primary law of classical logic, the law of excluded middle, does not apply. Journey is a dialogic work, even though ideological reasons for and against foreign travels are not equal.
Keywords: formal logic; critical thinking; Ignacy Krasicki; interpretation